2015
DOI: 10.1021/acs.jpcb.5b06073
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Correlations in Cyanobiphenyl-Based Dimer-Like Mesogens

Abstract: In this contribution, we present the results of our extensive investigations on the synthesis and phase behavior of five series of dimer-like compounds formed by covalently linking a promesogenic, cyanobiphenyl core, with a nonmesogenic N-(n-alkyl)-salicylaldimine segment via an oxy(oligomethylene)oxy spacer of varying length and parity. This work is a continuation of our previous short study where the occurrence of re-entrant nematic (Nre) phase seemed to be vitally dependent on the parity of the spacer and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…Transitions from the twist-bend nematic to smectic phases are rare, although examples exist, and it is worth speculating as to whether or not re-entrant N TB phases can exist; examples of both re-entrant nematic and re-entrant smectic phases in dimers have been reported, 138,139 but to date such behaviour has not been observed for the N TB phase.…”
Section: Discussionmentioning
confidence: 99%
“…Transitions from the twist-bend nematic to smectic phases are rare, although examples exist, and it is worth speculating as to whether or not re-entrant N TB phases can exist; examples of both re-entrant nematic and re-entrant smectic phases in dimers have been reported, 138,139 but to date such behaviour has not been observed for the N TB phase.…”
Section: Discussionmentioning
confidence: 99%
“…Column chromatography was conducted using silica gel (FUJIFILM Wako Pure Chemical Corporation, Wakogel ® 60N, 38-100 μm; Osaka, Japan) and thin layer chromatography (TLC) was performed on silica gel TLC plates (Merck, Silica gel 60F254; Kenilworth, NJ, USA). Based on the knowledge we acquired on the photophysical behavior of such fluorinated π-conjugated molecules, e.g., 1a, we envisioned that dyads 2a-f consisting of two fluorinated tolane-based luminophore 1a and an alkylene linkage as a spacer could take up a different molecular geometry depending on the linkage length, based on factors such as the odd-even effect [29][30][31][32]. Therefore, we constructed various molecular aggregated structures to display various photophysical behaviors.…”
Section: Generalmentioning
confidence: 99%
“…With deep investigations, interestingly, the PL behavior of 1a and the nonfluorinated analogue on the aromatic ring was found to change with an alteration of the molecular aggregated structures in the crystalline lattice; it was shown that fluorine atoms attached to an aromatic ring offering control over the molecular aggregated structure and photophysical behavior. Based on the knowledge we acquired on the photophysical behavior of such fluorinated πconjugated molecules, e.g., 1a, we envisioned that dyads 2a-f consisting of two fluorinated tolanebased luminophore 1a and an alkylene linkage as a spacer could take up a different molecular geometry depending on the linkage length, based on factors such as the odd-even effect [29][30][31][32]. Therefore, we constructed various molecular aggregated structures to display various photophysical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…LC dimers have now attracted considerable research interest over a prolonged period, [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] not only because they can be used as models of thermotropic, semi-flexible main chain liquid crystalline, but also because of their quite different behaviours to conventional low-molar-mass LCs. LC dimers may be divided into two broad classes: symmetric [10,37,42] and nonsymmetric.…”
Section: Introductionmentioning
confidence: 99%